Rietveld Refinement in the Characterization of Crystalline Materials - Igor Djerdj (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
This Special Issue serves as a crystallographic forum covering various aspects of material science that have in common the use of the powerful Rietveld method in the analysis of the powder XRD patterns of investigated compounds.